Desain ruang memorial di kawasan bencana likuefaksi Balaroa - Idris, Syahril; Amar; Zainal; Bakri, Muhammad; Arief, Irdinal; Mardin, Rifai; Burhanuddin (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2026)
After the 7.4-magnitude earthquake, tsunami, and liquefaction disaster in September 2018, the Balaroa sub-district of Palu City was severely affected by liquefaction, which covered approximately 50 hectares with a perimeter of about 2.5 kilometres. This area was predominantly residential. Historically, residents of West Gunung Marawola avoided passing through this area when travelling to the Manonda Inpres Market, as the wheels of their carts would often become stuck. Consequently, the site was named Tagari Lonjo (a waterlogged and muddy area). This served as a form of natural mitigation, indicating that the site was unsuitable for habitation. This paper aims to establish a correlation between the initial conditions and the management of potential risks following the disaster. The research employs qualitative methods and utilises the Sendai Framework (as a conceptual foundation) and SWOT analysis (as a strategy formulation tool). The proposed design concept involves planning and utilisation of the former Balaroa liquefaction site, focusing not only on physical and ecological recovery but also on socio-economic revitalisation and strengthening resilience to future disasters. Based on the analysis, the geotechnical conditions of the former liquefaction site in Balaroa Village are recommended to be utilised as Ruang Natebuka Kodara (green open space) within land-use planning, with agrotourism potential that can foster economic self-reliance and help alleviate communal trauma. It is hoped that this paper will contribute particularly to education on mitigation and resilience, supporting regional sustainability through innovative post-disaster recovery strategies.